Identification of Distinct Unmutated Chronic Lymphocytic Leukemia Subsets in Mice Based on Their T Cell Dependency - Pal Singh, Simar; de Bruijn, Marjolein J. W.; de Almeida, Mariana P.; Meijers, Ruud W. J.; Nitschke, Lars; Langerak, Anton W.; Pillai, Saravanan Y.; Stadhouders, Ralph; Hendriks, Rudi W. (Frontiers in Immunology, 2018)
Chronic lymphocytic leukemia (CLL) can be divided into prognostically distinct subsets with stereotyped or non-stereotyped, mutated or unmutated B cell receptors (BCRs). Individual subsets vary in antigen specificity and origin, but the impact of antigenic pressure on the CLL BCR repertoire remains unknown. Here, we employed IgH.TEμ mice that spontaneously develop CLL, expressing mostly unmutated BCRs of which ~35% harbor VH11-2/Vkappa14-126 and recognize phosphatidylcholine. Proportions of VH11/Vkappa14-expressing CLL were increased in the absence of functional germinal centers in IgH.TEμ mice deficient for CD40L or activation-induced cytidine deaminase. Conversely, in vivo T cell-dependent immunization decreased the proportions of VH11/Vkappa14-expressing CLL. Furthermore, CLL onset was accelerated by enhanced BCR signaling in Siglec-G-/- mice or in mice expressing constitutively active Bruton’s tyrosine kinase. Transcriptional profiling revealed that VH11 and non-VH11 CLL differed in the upregulation of specific pathways implicated in cell signaling and metabolism. Interestingly, principal component analyses using the 148 differentially expressed genes revealed that VH11 and non-VH11 CLL clustered with BCR-stimulated and anti-CD40-stimulated B cells, respectively. We identified an expression signature consisting of 13 genes that were differentially expressed in a larger panel of T cell-dependent non-VH11 CLL compared with T cell-independent VH11/Vkappa14 or mutated IgH.TEμ CLL. Parallel differences in the expression of these 13 signature genes were observed between heterogeneous and stereotypic human unmutated CLL. Our findings provide evidence for two distinct unmutated CLL subsets with a specific transcriptional signature: one is T cell-independent and B-1 cell-derived while the other arises upon antigen stimulation in the context of T-cell help.